Performance of Muara Enim Regency Regional Civil Servants at the Tourism and Creative Economy Office - Puspita, Della Ade; Prakoso, Lukman Yudho (Indonesian Journal of Interdisciplinary Research in Science and Technology, 2023)
The purpose of this research is to identify variables and employee performance. This has an impact on the output of workers at the Tourism and Creative Economy Department. Descriptive research is the methodology used, qualitative research aims to explain the variables studied, in this case the employees of the Department of Tourism and Creative Economy, by providing explanations of all events obtained in the field and by explaining problem solving based on the data obtained. Data collection was carried out using methods and strategies from library research. Direct object observation, direct source interviews, and documentation constitute field research. The overall picture obtained from research findings is that it is not yet operating optimally due to employee performance reasons. According to research findings, the Tourism and Creative Economy Department requires additional Human Resources (HR) who must have skills, experience and be diligent. Low staffing levels are indicated by the large number of employees who often leave the workplace during working hours and arrive late. Both strict punishments for workers who lack discipline in carrying out their work and training to improve employee talents are needed to improve employee performance in carrying out their obligations.